High genomic differentiation and limited gene flow indicate recent cryptic speciation within the genus Laspinema (cyanobacteria) - Stanojković, Aleksandar; Skoupý, Svatopluk; Škaloud, Pavel; Dvořák, Petr (Frontiers in Microbiology, 2022)
The sympatric occurrence of closely related lineages displaying conserved morphological and ecological traits is often characteristic of free-living microbes. Gene flow, recombination, selection, and mutations govern the genetic variability between these cryptic lineages and drive their differentiation. However, sequencing conservative molecular markers (e.g., 16S rRNA) coupled with insufficient population-level sampling hindered the study of intra-species genetic diversity and speciation in cyanobacteria. We used phylogenomics and a population genomic approach to investigate the extent of local genomic diversity and the mechanisms underlying sympatric speciation of Laspinema thermale. We found two cryptic lineages of Laspinema. The lineages were highly genetically diverse, with recombination occurring more frequently within than between them. That suggests the existence of a barrier to gene flow, which further maintains divergence. Genomic regions of high population differentiation harbored genes associated with possible adaptations to high/low light conditions and stress stimuli, although with a weak diversifying selection. Overall, the diversification of Laspinema species might have been affected by both genomic and ecological processes.